Method for producing copper-aluminum composite plate strip and application of copper-aluminum composite plate strip

By finely controlling the annealing and process flow, the problem of insufficient thickness of copper-aluminum composite plate belt is solved, and thinner and tougher copper-aluminum composite plate belt is realized, which is suitable for the electronics field and reduces production costs.

CN119265495APending Publication Date: 2025-01-07LUOYANG COPPER ONE METAL MATERIAL DEVELOPS CO LTD

Patent Information

Application Number
CN202411293777.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-30
Filing Date
2024-09-14
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In the production of copper-aluminum composite panel tapes, the thickness obtained by the prior art is still not small enough to be effectively applied to the electronics field.

Method used

Adopt periodic nitrogen protective cover furnace annealing treatment, oxygen-enhancing treatment of copper materials, semi-melted aluminum and copper materials with high pressure continuous casting and rolling, cold rolling treatment and foil rolling processes, finely control the annealing temperature and time, combined with the foil rolling process , make copper-aluminum composite panel tape with thinner thickness.

Benefits of technology

The thickness of the copper-aluminum composite plate tape is reduced to 0.01-0.035mm, which improves its toughness, reduces the possibility of separation of the aluminum layer from the copper layer, and expands the width range, improves production efficiency and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265495A_ABST
    Figure CN119265495A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of copper-aluminum composite plate strips, in particular to a method for producing a copper-aluminum composite plate strip and application of the copper-aluminum composite plate strip, and the method comprises the following steps: carrying out periodic nitrogen protection cover type furnace annealing treatment on a cold-rolled copper-aluminum composite blank, heating to 170-190 DEG C at room temperature, blowing and removing oil for 1.5-2.5 hours, annealing at 200-300 DEG C, and keeping the temperature for 3-8 hours, the prepared copper-aluminum composite plate strip is applied to a bipolar current collector. The method has the advantages that the special annealing process is adopted, the thickness of the intermetallic compound in the copper-aluminum composite plate strip is reduced, the foil rolling process is combined, the thinner copper-aluminum composite foil can be obtained through foil rolling, and the thickness range of the copper-aluminum composite foil is 0.01-0.035 mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper-aluminum composite plates and strips, in particular to a method for producing copper-aluminum composite plates and strips and application thereof. Background Art

[0002] Copper-aluminum composite foil is a copper-aluminum composite strip with extremely small thickness.

[0003] Copper-aluminum composite foil has important applications in the field of electronics. It has good electrical and thermal conductivity and can be used to manufacture wires, circuit boards, and heat sinks for electronic components. The electrical conductivity of copper-aluminum composite foil is better than that of pure aluminum foil, and its thermal conductivity is better than that of pure copper foil. Therefore, it can optimize circuits and heat dissipation in electronic equipment, thereby improving the performance and reliability of the equipment.

[0004] At present, the methods for producing copper-aluminum composite sheets include explosive compounding, double-mold casting, hydrostatic extrusion, electroplating process and continuous rolling. Among them, continuous rolling is a method for producing copper-aluminum composite sheets in which the production process is more energy-saving and easier to control.

[0005] For example, CN108237151B discloses an ultra-thin copper-clad copper-aluminum composite material and a production method thereof, which includes: compounding a layer of aluminum coating on the surface of the aluminum layer of the copper-aluminum composite plate and strip to obtain a copper-aluminum composite billet, and cold rolling the resultant; the state of the aluminum layer material of the copper-aluminum composite material is O state, the grade of the copper layer material is T2, and the aluminum layer material is a 1 series, 3 series or 8 series deformed aluminum alloy; the thickness of the copper-aluminum composite plate and strip is 0.8 to 6.0 mm, and compounding a layer of aluminum coating on the surface of the aluminum layer of the copper-aluminum composite plate and strip is specifically as follows: contacting the aluminum layer of the copper-aluminum composite plate and strip with a semi-molten aluminum alloy liquid, and then performing oxygen-free continuous casting and rolling to obtain the copper-aluminum composite billet.

[0006] In order to reduce the thickness of copper-aluminum composite plates and strips and produce copper-aluminum composite foils, Chinese patent publication number CN109078983B discloses a method for preparing ultra-thin copper-aluminum composite foils. The multi-pass rolling + intermediate annealing process avoids the disadvantages of high explosion energy and poor welding performance. The prepared copper-aluminum composite foil has a thickness of only 0.06 mm. The interface of the copper-aluminum composite foil with a thickness of 0.06 mm achieves metallurgical bonding, which can show the advantages of high conductivity, high thermal conductivity, corrosion resistance and low cost of aluminum-copper composite plates.

[0007] The problem with the prior art is that the thickness of the copper-aluminum composite material obtained by continuous rolling is not small enough and cannot be well applied in the electronic field. Summary of the invention

[0008] In order to overcome the deficiencies of the prior art, the present invention provides a method for producing a copper-aluminum composite plate and strip and its use.

[0009] The technical solution adopted by the present invention to solve its technical problem is:

[0010] A method for producing a copper-aluminum composite plate and strip comprises step (6), wherein the step (6) is to subject the cold-rolled copper-aluminum composite blank to periodic nitrogen protection hood furnace annealing treatment, raise the room temperature to 170-190°C, blow and remove oil for 1.5-2.5 hours, anneal at a temperature of 200-300°C, and keep warm for 3-8 hours.

[0011] The following steps are also included:

[0012] (1) Red copper or oxygen-free copper is subjected to oxygenation treatment so that the oxygen content of the red copper or oxygen-free copper is 50ppm-500ppm, thereby obtaining a copper material.

[0013] (2) The aluminum ingot is melted at 700-850°C, and Si, Fe, Cu, and Mn are added to melt, refined and degassed, and the molten liquid after refining and degassing is allowed to stand at 690-820°C for 5-15 minutes, and then poured into a preheated casting nozzle. The cast aluminum alloy liquid is cooled and crystallized to a semi-molten state to obtain a semi-molten aluminum material.

[0014] (3) After the copper material of step (1) is subjected to alkaline washing and degreasing treatment, it is single-sided polished until there is no oxide layer on the surface. After polishing, the copper material is heated to 230-250° C.

[0015] (4) The semi-molten aluminum material in step (2) is brought into contact with the polished surface of the copper material in step (3), and oxygen-free high-pressure continuous casting and rolling are performed to obtain a copper-aluminum composite billet.

[0016] (5) The copper-aluminum composite billet of step (4) is subjected to cold rolling treatment, and the total processing rate of the cold rolling treatment is 15-75%.

[0017] After step (6), the step further includes: rapidly cooling the furnace to below 65° C. and taking the furnace out of the furnace.

[0018] The thickness of the composite blank in step (4) is 6.5-8.0 mm; the thickness of the composite blank after cold rolling in step (5) is 0.15-1.0 mm; the annealing time in step (6) is 10-30 hours, and the annealing temperature is 200-240°C.

[0019] The method further comprises the step (7): rolling the blank foil after annealing in the step (6) to a thickness of 0.01-0.035 mm to obtain a foil material; the foil rolling speed is 400-1300 m / min, the foil rolling pressure is 130-190 tons, and the tension is 1400-2200 N.

[0020] In the step (4), the semi-molten aluminum material is in contact with both the upper and lower surfaces of the copper material.

[0021] The width of the copper-aluminum composite plate and strip ranges from 800 to 1350 mm.

[0022] The thickness of the intermetallic compound in the copper-aluminum composite plate and strip is 300-1000nm.

[0023] The copper-aluminum composite plate strip comprises a copper layer and an aluminum layer, and the thickness of the copper layer accounts for 15%-40% of the thickness of the copper-aluminum composite plate strip.

[0024] A use of the copper-aluminum composite strip obtained by the method as described above, wherein the copper-aluminum composite strip is applied to a bipolar current collector.

[0025] The beneficial effects of the present invention are:

[0026] A special annealing process is adopted, and compared with the prior art, the annealing control is more precise, so that the thickness of the intermetallic compound in the copper-aluminum composite plate and strip is reduced. Combined with the foil rolling process, a thinner copper-aluminum composite foil can be rolled out, and the thickness range is 0.01-0.035mm. The lower thickness can bring better toughness, so that the copper-aluminum composite plate and strip of the present invention is suitable for the electronic field;

[0027] The thickness of the intermetallic compound in the copper-aluminum composite strip of the present invention is 300-1000 nm, which is relatively low. The relatively low thickness of the intermetallic compound can also improve the toughness of the copper-aluminum composite strip and reduce the possibility of separation of the aluminum layer and the copper layer during the bending process.

[0028] The copper-aluminum composite plate and strip of the present invention has a width range of 800-1350 mm, which is relatively wide. Increasing the width range means improving the production efficiency of the copper-aluminum composite plate and strip and reducing the production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0030] Figure 1 This is a photo of the thickness detection of the intermetallic compound of sample 1;

[0031] Figure 2 This is a photo of the thickness detection of the intermetallic compound of sample 2;

[0032] Figure 3 This is a photo of the thickness detection of the intermetallic compound of sample 3;

[0033] Figure 4 is the thickness and width data table of samples 1-6;

[0034] Figure 5 These are the bending test results of samples 1-6. DETAILED DESCRIPTION

[0035] In all embodiments of the present invention, unless otherwise specified about temperature and pressure, all are at room temperature and pressure, and unless otherwise specified about the use of equipment, all can be used according to conventional settings.

[0036] To make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with specific implementation methods. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0037] Combination Figures 1 to 5 :

[0038] In the following embodiments, the red copper or oxygen-free copper is made of copper material with grade T2.

[0039] Embodiment 1, a method for producing a copper-aluminum composite plate and strip, comprising the following steps:

[0040] (1) Red copper or oxygen-free copper is subjected to oxygenation treatment so that the oxygen content of the red copper or oxygen-free copper is 50ppm-500ppm, thereby obtaining a copper material.

[0041] (2) The aluminum ingot is melted at 700°C, and Si, Fe, Cu, and Mn are added to melt and refined and degassed. The molten liquid after refining and degassing is allowed to stand at 790°C for 5 minutes and then poured into a preheated casting nozzle. The cast aluminum alloy liquid is cooled and crystallized to a semi-molten state to obtain a semi-molten aluminum material.

[0042] (3) After the copper material of step (1) is subjected to alkaline washing and degreasing treatment, the upper surface is polished until there is no oxide layer on the surface. After the polishing is completed, the copper material is heated to 230° C.

[0043] (4) The semi-molten aluminum material in step (2) is brought into contact with the upper surface of the copper material in step (3), and oxygen-free high-pressure continuous casting and rolling are performed to obtain a copper-aluminum composite billet, wherein the thickness of the composite billet is 7.0 mm, wherein the thickness of the copper layer accounts for 15% of the thickness of the composite billet.

[0044] (5) The copper-aluminum composite billet of step (4) is cold rolled, the total processing rate of the cold rolling treatment is 60%, and the thickness of the composite billet after the cold rolling treatment is 0.15 mm.

[0045] (6) The cold-rolled copper-aluminum composite billet is subjected to periodic nitrogen protection hood furnace annealing treatment, the room temperature is raised to 180°C, the oil is purged and removed for 2 hours, the annealing temperature is 300°C, the annealing time is 10 hours, the heat preservation is 5 hours, and the billet is quickly cooled to below 60°C and taken out of the furnace.

[0046] (7) The blank foil after annealing in step (6) is rolled to a thickness of 0.01 mm to obtain a foil material; the foil rolling speed is 1300 m / min, the foil rolling pressure is 190 tons, and the tension is 1400 N.

[0047] (8) The foil material of step (7) is trimmed to obtain sample 1. The thickness and width of sample 1 are as follows: the thickness of sample 1 is 0.010 mm, and the width is 940 mm.

[0048] Embodiment 2, a method for producing a copper-aluminum composite plate and strip, comprising the following steps:

[0049] (1) Red copper or oxygen-free copper is subjected to oxygenation treatment so that the oxygen content of the red copper or oxygen-free copper is 50ppm-500ppm, thereby obtaining a copper material.

[0050] (2) The aluminum ingot is melted at 700°C, and Si, Fe, Cu, and Mn are added to melt and refined and degassed. The molten liquid after refining and degassing is allowed to stand at 790°C for 5 minutes and then poured into a preheated casting nozzle. The cast aluminum alloy liquid is cooled and crystallized to a semi-molten state to obtain a semi-molten aluminum material.

[0051] (3) After the copper material of step (1) is subjected to alkaline washing and degreasing treatment, it is single-sided polished until there is no oxide layer on the surface. After polishing, the copper material is heated to 230° C.

[0052] (4) The semi-molten aluminum material in step (2) is brought into contact with the polished surface of the copper material in step (3), and oxygen-free high-pressure continuous casting and rolling are performed to obtain a copper-aluminum composite billet, wherein the thickness of the composite billet is 8.0 mm, wherein the thickness of the copper layer accounts for 20% of the thickness of the composite billet.

[0053] (5) The copper-aluminum composite billet of step (4) is cold rolled, the total processing rate of the cold rolling treatment is 60%, and the thickness of the composite billet after the cold rolling treatment is 0.6 mm.

[0054] (6) The cold-rolled copper-aluminum composite billet is subjected to periodic annealing treatment in a nitrogen protection hood furnace. The temperature is raised from room temperature to 180°C, and the billet is purged and degreased for 2 hours. The annealing temperature is 240°C, the annealing time is 20 hours, and the billet is kept at this temperature for 5 hours. The billet is then rapidly cooled to below 60°C and taken out of the furnace.

[0055] (7) The blank foil after annealing in step (6) is rolled to a thickness of 0.025 mm to obtain a foil material; the foil rolling speed is 650 m / min, the foil rolling pressure is 160 tons, and the tension is 1500 N.

[0056] (8) The foil material of step (7) is trimmed to obtain sample 2. The thickness and width of sample 2 are as follows: the thickness of sample 2 is 0.025 mm, and the width is 1350 mm.

[0057] Embodiment 3, a method for producing a copper-aluminum composite plate and strip, comprising the following steps:

[0058] (1) Red copper or oxygen-free copper is subjected to oxygenation treatment so that the oxygen content of the red copper or oxygen-free copper is 50ppm-500ppm, thereby obtaining a copper material.

[0059] (2) The aluminum ingot is melted at 700°C, and Si, Fe, Cu, and Mn are added to melt and refined and degassed. The molten liquid after refining and degassing is allowed to stand at 790°C for 5 minutes and then poured into a preheated casting nozzle. The cast aluminum alloy liquid is cooled and crystallized to a semi-molten state to obtain a semi-molten aluminum material.

[0060] (3) After the copper material of step (1) is subjected to alkaline washing and degreasing treatment, it is single-sided polished until there is no oxide layer on the surface. After polishing, the copper material is heated to 230° C.

[0061] (4) The semi-molten aluminum material in step (2) is brought into contact with the polished surface of the copper material in step (3), and oxygen-free high-pressure continuous casting and rolling are performed to obtain a copper-aluminum composite billet, wherein the thickness of the composite billet is 6.5 mm, wherein the thickness of the copper layer accounts for 40% of the thickness of the composite billet.

[0062] (5) The copper-aluminum composite billet of step (4) is cold rolled, the total processing rate of the cold rolling treatment is 60%, and the thickness of the composite billet after the cold rolling treatment is 1.0 mm.

[0063] (6) The cold-rolled copper-aluminum composite billet is subjected to periodic annealing treatment in a nitrogen protection hood furnace. The temperature is raised from room temperature to 180°C, and the billet is purged and degreased for 2 hours. The annealing temperature is 190°C, the annealing time is 30 hours, and the billet is kept at this temperature for 5 hours. The billet is then rapidly cooled to below 60°C and taken out of the furnace.

[0064] (7) The blank foil after annealing in step (6) is rolled to a thickness of 0.033 mm to obtain a foil material; the foil rolling speed is 400 m / min, the foil rolling pressure is 130 tons, and the tension is 2200 N.

[0065] (8) The foil material of step (7) is trimmed to obtain sample 3. The thickness and width of sample 3 are 0.033 mm and 1310 mm respectively.

[0066] Embodiment 4, a method for producing a copper-aluminum composite plate and strip, comprising the following steps:

[0067] (1) Red copper or oxygen-free copper is subjected to oxygenation treatment so that the oxygen content of the red copper or oxygen-free copper is 50ppm-500ppm, thereby obtaining a copper material.

[0068] (2) The aluminum ingot is melted at 700°C, and Si, Fe, Cu, and Mn are added to melt and refined and degassed. The molten liquid after refining and degassing is allowed to stand at 790°C for 5 minutes and then poured into a preheated casting nozzle. The cast aluminum alloy liquid is cooled and crystallized to a semi-molten state to obtain a semi-molten aluminum material.

[0069] (3) After the copper material of step (1) is subjected to alkaline washing and degreasing treatment, the upper and lower surfaces are polished until there is no oxide layer on the surface. After the polishing is completed, the copper material is heated to 230° C.

[0070] (4) The semi-molten aluminum material in step (2) is brought into contact with the upper surface and the lower surface of the copper material in step (3), and oxygen-free high-pressure continuous casting and rolling are performed to obtain a copper-aluminum composite billet, wherein the thickness of the composite billet is 7.0 mm, wherein the thickness of the copper layer accounts for 15% of the thickness of the composite billet.

[0071] (5) The copper-aluminum composite billet of step (4) is cold rolled, the total processing rate of the cold rolling treatment is 60%, and the thickness of the composite billet after the cold rolling treatment is 0.15 mm.

[0072] (6) The cold-rolled copper-aluminum composite billet is subjected to periodic nitrogen protection hood furnace annealing treatment, the room temperature is raised to 180°C, the oil is purged and removed for 2 hours, the annealing temperature is 300°C, the annealing time is 10 hours, the heat preservation is 5 hours, and the billet is quickly cooled to below 60°C and taken out of the furnace.

[0073] (7) Roll the annealed blank foil in step (6) to a thickness of 0.01-0.035 mm to obtain a foil material; the foil rolling speed is 1300 m / min, the foil rolling pressure is 190 tons, and the tension is 1400 N.

[0074] (8) The foil material of step (7) is trimmed to obtain sample 4. The thickness and width of sample 4 are 0.011 mm and 996 mm, respectively.

[0075] Embodiment 5, a method for producing a copper-aluminum composite plate and strip, comprising the following steps:

[0076] (1) Red copper or oxygen-free copper is subjected to oxygenation treatment so that the oxygen content of the red copper or oxygen-free copper is 50ppm-500ppm, thereby obtaining a copper material.

[0077] (2) The aluminum ingot is melted at 700°C, and Si, Fe, Cu, and Mn are added to melt and refined and degassed. The molten liquid after refining and degassing is allowed to stand at 790°C for 5 minutes and then poured into a preheated casting nozzle. The cast aluminum alloy liquid is cooled and crystallized to a semi-molten state to obtain a semi-molten aluminum material.

[0078] (3) After the copper material of step (1) is subjected to alkaline washing and degreasing treatment, the upper and lower surfaces are polished until there is no oxide layer on the surface. After the polishing is completed, the copper material is heated to 230° C.

[0079] (4) The semi-molten aluminum material in step (2) is brought into contact with the upper surface and the lower surface of the copper material in step (3), and oxygen-free high-pressure continuous casting and rolling are performed to obtain a copper-aluminum composite billet, wherein the thickness of the composite billet is 8.0 mm, wherein the thickness of the copper layer accounts for 20% of the thickness of the composite billet.

[0080] (5) The copper-aluminum composite billet of step (4) is cold rolled, the total processing rate of the cold rolling treatment is 60%, and the thickness of the composite billet after the cold rolling treatment is 0.6 mm.

[0081] (6) The cold-rolled copper-aluminum composite billet is subjected to periodic annealing treatment in a nitrogen protection hood furnace. The temperature is raised from room temperature to 180°C, and the billet is purged and degreased for 2 hours. The annealing temperature is 240°C, the annealing time is 20 hours, and the billet is kept at this temperature for 5 hours. The billet is then rapidly cooled to below 60°C and taken out of the furnace.

[0082] (7) The blank foil after annealing in step (6) is rolled to a thickness of 0.024 mm to obtain a foil material; the foil rolling speed is 650 m / min, the foil rolling pressure is 160 tons, and the tension is 1500 N.

[0083] (8) The foil material of step (7) is trimmed to obtain sample 5. The thickness and width of sample 5 are as follows: the thickness of sample 5 is 0.024 mm, and the width is 800 mm.

[0084] Embodiment 6, a method for producing a copper-aluminum composite plate and strip, comprising the following steps:

[0085] (1) Red copper or oxygen-free copper is subjected to oxygenation treatment so that the oxygen content of the red copper or oxygen-free copper is 50ppm-500ppm, thereby obtaining a copper material.

[0086] (2) The aluminum ingot is melted at 700°C, and Si, Fe, Cu, and Mn are added to melt and refined and degassed. The molten liquid after refining and degassing is allowed to stand at 790°C for 5 minutes and then poured into a preheated casting nozzle. The cast aluminum alloy liquid is cooled and crystallized to a semi-molten state to obtain a semi-molten aluminum material.

[0087] (3) After the copper material of step (1) is subjected to alkaline washing and degreasing treatment, the upper and lower surfaces are polished until there is no oxide layer on the surface. After the polishing is completed, the copper material is heated to 230° C.

[0088] (4) The semi-molten aluminum material in step (2) is brought into contact with the upper surface and the lower surface of the copper material in step (3), and oxygen-free high-pressure continuous casting and rolling are performed to obtain a copper-aluminum composite billet, wherein the thickness of the composite billet is 6.5 mm, wherein the thickness of the copper layer accounts for 40% of the thickness of the composite billet.

[0089] (5) The copper-aluminum composite billet of step (4) is cold rolled, the total processing rate of the cold rolling treatment is 60%, and the thickness of the composite billet after the cold rolling treatment is 1.0 mm.

[0090] (6) The cold-rolled copper-aluminum composite billet is subjected to periodic annealing treatment in a nitrogen protection hood furnace. The temperature is raised from room temperature to 180°C, and the billet is purged and degreased for 2 hours. The annealing temperature is 190°C, the annealing time is 30 hours, and the billet is kept at this temperature for 5 hours. The billet is then rapidly cooled to below 60°C and taken out of the furnace.

[0091] (7) The blank foil after annealing in step (6) is rolled to a thickness of 0.035 mm to obtain a foil material; the foil rolling speed is 400 m / min, the foil rolling pressure is 130 tons, and the tension is 2200 N.

[0092] (8) The foil material of step (7) is trimmed to obtain sample 6. The thickness and width of sample 6 are as follows: the thickness of sample 6 is 0.035 mm, and the width is 1100 mm.

[0093] In the above embodiment, the specific annealing steps can be: the staff inspects the incoming materials to ensure that the colors of the two surfaces of the blank are uniform, puts the blank into the annealing furnace, evacuates the furnace and fills it with nitrogen, and after the inflation is completed, hangs the heating cover, starts heating, and heats to 190-300°C within 2 hours, and then anneals for 10-30 hours at a temperature of 10-30 hours, stops heating, hangs the heating cover, replaces the cooling cover, cools to room temperature, hangs the cooling cover, and then hangs the blank out of the annealing furnace.

[0094] Figure 4 The thickness and width data of samples 1 to 6. The thickness range of samples 1 to 6 falls within the range of 0.01-0.035 mm, and the width range falls within the range of 800-1350 mm. They have the characteristics of small thickness and large width, are suitable for the electronic field, and have lower production costs than the existing technology.

[0095] Bending test: Take the above samples 1-6, cut a longitudinal width of 200mm and a length of 250mm, and cut it into 5 15*150mm long longitudinal strips using a sampler. Use a folding endurance tester to measure five times and take the average value. The measuring angle is set to 135° and the bending speed is set to 175 times / minute. The test results are as follows: Figure 5The higher the average number of bending times, the better the toughness of the sample, which is one of the benefits of a thin sample thickness. At the same time, better toughness means a lower possibility of separation between the aluminum layer and the copper layer during the bending process, and a higher reliability of the sample, which is one of the manifestations of a thinner intermetallic compound thickness in the sample.

[0096] Reference Figure 1-3 , is a test photograph of the thickness of the intermetallic compound of samples 1 to 3 of the present invention. The thickness of the intermetallic compound in sample 1 of the present invention does not exceed 323.8nm, the thickness of the intermetallic compound in sample 2 does not exceed 401.9nm, and the thickness of the intermetallic compound in sample 3 does not exceed 815.0nm.

[0097] The thickness of the intermetallic compound of the ultra-thin copper-aluminum composite foil disclosed in the invention of prior art publication number CN109078983B is close to 20 microns, indicating that the copper-aluminum composite foil of the present invention has a more excellent internal structure.

[0098] The applicant mainly conducted detailed research and experiments on the embodiments with annealing temperatures of 300°C, 240°C and 190°C, obtained detailed experimental data, and obtained detailed and complete experimental data recorded in this application. Preliminary research was also conducted on other annealing temperatures within 190°C-300°C, but detailed and complete experimental data have not yet been formed. According to the existing data, the production method with an annealing temperature of 200°C can further reduce the thickness of intermetallic compounds in the copper-aluminum composite plate and strip compared to 190°C, and can roll out copper-aluminum composite foil with thinner thickness.

[0099] The above implementation modes cannot limit the protection scope of the invention. Without departing from the spirit and scope of the invention, the invention may have various changes and improvements, and these changes and improvements all fall within the scope of the invention claimed for protection.

Claims

1. A method for producing a copper-aluminum composite strip, characterized in that: The method comprises step (6), wherein the step (6) is: subjecting the cold-rolled copper-aluminum composite blank to periodic nitrogen protection hood furnace annealing treatment, heating the room temperature to 170-190° C., blowing and degreasing for 1.5-2.5 hours, the annealing temperature is 200-300° C., and the temperature is kept for 3-8 hours.

2. A method for producing a copper-aluminum composite strip according to claim 1, characterized in that: The following steps are also included: (1) subjecting red copper or oxygen-free copper to an oxygen-enhancing treatment so that the oxygen content of the red copper or oxygen-free copper is 50 ppm to 500 ppm, thereby obtaining a copper material; (2) melting the aluminum ingot at 700-850°C, adding Si, Fe, Cu, and Mn to melt, refining and degassing, letting the refined and degassed molten liquid stand at 690-820°C for 5-15 minutes, and then pouring it into a preheated casting nozzle. The cast aluminum alloy liquid is cooled and crystallized to a semi-molten state to obtain a semi-molten aluminum material; (3) After the copper material of step (1) is subjected to alkaline washing and degreasing treatment, it is single-sided polished until there is no oxide layer on the surface, and the copper material is heated to 230-250° C. after polishing; (4) placing the semi-molten aluminum material in step (2) in contact with the polished surface of the copper material in step (3), and performing oxygen-free high-pressure continuous casting and rolling to obtain a copper-aluminum composite billet; (5) The copper-aluminum composite billet of step (4) is subjected to cold rolling treatment, and the total processing rate of the cold rolling treatment is 15-75%.

3. A method for producing a copper-aluminum composite strip according to claim 2, characterized in that: After step (6), the step further includes: rapidly cooling the furnace to below 65° C. and taking the furnace out of the furnace.

4. A method for producing a copper-aluminum composite plate and strip according to claim 3, characterized in that: The thickness of the composite blank in step (4) is 6.5-8.0 mm; the thickness of the composite blank after cold rolling in step (5) is 0.15-1.0 mm; the annealing time in step (6) is 10-30 hours, and the annealing temperature is 200-240°C.

5. A method for producing a copper-aluminum composite plate and strip according to claim 4, characterized in that: The method further comprises the step (7): rolling the blank foil after annealing in the step (6) to a thickness of 0.01-0.035 mm to obtain a foil material; the foil rolling speed is 400-1300 m / min, the foil rolling pressure is 130-190 tons, and the tension is 1400-2200 N.

6. A method for producing a copper-aluminum composite strip according to claim 3, characterized in that: In the step (4), the semi-molten aluminum material is in contact with both the upper and lower surfaces of the copper material.

7. A method for producing a copper-aluminum composite strip according to claim 3, characterized in that: The width of the copper-aluminum composite plate and strip ranges from 800 to 1350 mm.

8. A method for producing a copper-aluminum composite plate and strip according to claim 3, characterized in that: The thickness of the intermetallic compound in the copper-aluminum composite plate and strip is 300-1000nm.

9. A method for producing a copper-aluminum composite plate and strip according to claim 3, characterized in that: The copper-aluminum composite plate strip comprises a copper layer and an aluminum layer, and the ratio of the thickness of the copper layer to the thickness of the copper-aluminum composite plate strip is 15%-40%.

10. Use of the copper-aluminum composite strip obtained by the method according to any one of claims 1 to 9, characterized in that: The copper-aluminum composite strip is used for bipolar current collector.

Citation Information

Patent Citations

  • An ultrathin copper-copper composite material and its production method

    CN108237151B

  • A method for preparing ultrathin copper-aluminum composite foil

    CN109078983B

Cited By

  • Preparation method of copper-aluminum bimetallic composite material

    CN121110032A